![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
\(\left(n^2-9n+7\right)⋮\left(n-9\right)\Rightarrow\left[\left(n-9\right)n+7\right]⋮\left(n-9\right)\)
Mà ta có:\(\left(n-9\right)n⋮\left(n-9\right)\Rightarrow7⋮\left(n-9\right)\)
⇒\(\left(n-9\right)\inƯ\left(7\right)\)
Ta có bảng sau:
\(n-9\) | \(-7\) | \(-1\) | 1 | 7 |
n | 2 | 8 | 10 | 16 |
Ta có:
(n2−9n+7)⋮(n−9)⇒[(n−9)n+7]⋮(n−9)
Mà ta có:(n−9)n⋮(n−9)⇒7⋮(n−9)
⇒(n−9)∈Ư(7)
Ta có bảng sau:
n−9 | −7 | −1 | 1 | 7 |
n | 2 | 8 | 10 | 16 |
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : n2 - 9n + 7 = n.n - 9n + 7 = n ( n - 9 ) + 7
Để n2 - 9n + 7 \(⋮\)n - 9
=> n ( n - 9 ) + 7 \(⋮\)n - 9
=> 7 \(⋮\)n - 9
=> n - 9 \(\in\)Ư( 7 ) = ( 1 ; 7 )
=> n \(\in\)( 10 ; 16 )
~ HỌC TỐT ~
![](https://rs.olm.vn/images/avt/0.png?1311)
a) n + 7 chia hết cho n + 2
n + 2 + 5 chia hết cho n + 2
5 chia hết cho n + 2
n + 2 thuộc U(5) = {-5;-1;1;5}
n thuộc {-7 ; -3 ; -1 ; 3}
b) 2n + 15 chia hết cho n + 2
2n + 4+ 11 chia hết cho n + 2
11 chia hết cho n + 2
n + 2 thuộc U(11) = {-11; -1 ; 1 ; 11}
n thuộc {-13 ; -3 ; -1 ; 9}
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:
n^2
n=-1;3;5;9